Fostering the development of non-technical competencies in medical learners through patient engagement: a rapid review - Massé, Julie; Beaura, Stéphanie; Tremblay, Marie-Claude (Canadian Medical Education Journal, 2023)
Background: To train physicians who will respond to patients’ evolving needs and expectations, medical schools must seek educational strategies to foster the development of non-technical competencies in students. This article aims to synthetize studies that focus on patient engagement in medical training as a promising strategy to foster the development of those competencies. Methods: We conducted a rapid review of the literature to synthetize primary quantitative, qualitative and mixed studies (January 2000-January 2022) describing patient engagement interventions in medical education and reporting non-technical learning outcomes. Studies were extracted from Medline and ERIC. Two independent reviewers were involved in study selection and data extraction. A narrative synthesis of results was performed. Results: Of the 3875 identified, 24 met the inclusion criteria and were retained. We found evidence of a range of non-technical educational outcomes (e. g. attitudinal changes, new knowledge and understanding). Studies also described various approaches regarding patient recruitment, preparation, and support and participation design (e.g., contact duration, learning environment, patient autonomy, and format). Some emerging practical suggestions are proposed. Conclusion: Our results suggest that patient engagement in medical education can be a valuable means to foster a range of non-technical competencies, as well as formative and critical reflexivity. They also suggest conditions under which patient engagement practices can be more efficient in fostering non-instrumental patient roles in different educational contexts. This supports a plea for sensible and responsive interventional approaches.